The Effect of Marketing Promotion Strategy in Political Campaigns: A case Study for the Region of Attica. - Panagiotidou, Georgia; Chadjipadelis, Theodore (International Conference on Business and Economics - Hellenic Open University, 2023)
This research aims to analyze the political marketing strategy used in Greek regional elections of 2019 by candidate mayors, in the case of the region of Attica. Using advance methods of multivariate analysis such as Cluster analysis, Multiple Correspondence analysis and Principal component analysis we search for the strategy patterns used in terms of selecting promotion tools, prioritizing issues on the political agenda, and focusing on the candidate or the party. The analysis investigates the profiles of the candidates with reference to the above political marketing strategies and the connection to their political characteristics. Furthermore, the detected profiles and strategies are analyzed regarding their effect on the probability to be elected. (250 words max) EL Classifications: C38, D72, M31. Key words: Political Marketing; Political Analysis; Quantitative Methods; Municipal Elections; Political Campaigns